2011
DOI: 10.1016/j.eswa.2011.04.160
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of disorder with new computational tool: BVDEA

Abstract: Motivation:Recognizing that many intrinsically disordered regions in proteins play key roles in vital functions and also in some diseases, identification of the disordered regions has became a demanding process for structure prediction and functional characterization of proteins. Therefore, many studies have been motivated on accurate prediction of disorder. Mostly, machine learning techniques have been used for dealing with the prediction problem of disorder due to the capability of extracting the complex rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…They play a crucial role in a variety of important biological functions [4]. It is confirmed that some of these IDPs are related to many important regulatory functions in the cell [5], which have great impact on diseases such as Parkinson's disease, Alzheimer's disease and certain types of cancers [6]. Thus, accurately identifying IDPs is vital to obtaining more effective drug designs, better protein expressions and functional annotations.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…They play a crucial role in a variety of important biological functions [4]. It is confirmed that some of these IDPs are related to many important regulatory functions in the cell [5], which have great impact on diseases such as Parkinson's disease, Alzheimer's disease and certain types of cancers [6]. Thus, accurately identifying IDPs is vital to obtaining more effective drug designs, better protein expressions and functional annotations.…”
Section: Introductionmentioning
confidence: 91%
“…Thus, accurately identifying IDPs is vital to obtaining more effective drug designs, better protein expressions and functional annotations. However, it is often difficult to purify and crystallize the disordered protein regions [7], which makes the identification of IDPs usually both expensive and time-consuming with experimental approaches [6]. Thus, it is essential to predict IDPs through the computational approaches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other approaches include single-molecule fluorescence resonance energy transfer [174] , and atomic-force microscopy [175] . Traditional methods are expensive and time-consuming, especially in the aspects of purifying and crystallizing IDPRs; therefor researchers were holding their hopes on integrating state-of-the-art tools with advanced computational methods [176] , [177] . The latter can be divided to three approaches: The first one depends on physicochemical properties and propensity scales ( e.g.…”
Section: Other Modeling Challengesmentioning
confidence: 99%
“…The dataset DIS1616 is comprised of 1616 protein sequences with 2503 disordered regions and 2629 ordered regions, which include 186,069 disordered and 715,619 ordered residues. As a comparison, we run our schemes together with some existing schemes, such as DISOPRED2, RONN [24], DISPSSMP [25], Espritz and IsUnstructure [9] on the datasets R80 which are comprised of 78 protein sequences which include 2439 disordered and 19,412 ordered residues. The simulation results suggest that our scheme is at least as accurate as DiISPSSMP and requires computing only five features for each residue of a protein sequence, while the other need to compute 120 features for each residue, respectively.…”
Section: Introductionmentioning
confidence: 99%